Qualitative Research Design: A Discussion on its Types (Research Journal, 2024)
This review paper attempts to examine the key qualitative research designs, including case study, ethnography, phenomenology, grounded theory, and narrative inquiry. The main purpose of writing this paper is to provide basic idea and knowledge about major types of qualitative research design which are commonly used in the field of education. In order to prepare this, write up, different books and journal articles were consulted and reviewed. In this paper each design of qualitative research is analyzed for its methodological approach, underscoring its main objectives, sampling methods, data collection tools, and process of data interpretation. The paper also addresses the criticisms associated with each design, including concerns about generalizability, researcher bias, and the subjectivity of interpretation. This paper provides insights into the diverse methodologies within qualitative research and their contributions to understanding complex human and social phenomenon.